Penilaian Zona Kerentanan Air Tanah Terhadap Pencemaran dengan Metode SINTACS di Ranai (Pulau Bunguran) - Erik Febriarta; Dian Indah Shofarini (Jurnal Wilayah dan Lingkungan, 2021)
Bunguran Besar Island in the Natuna Islands, Riau Islands Province, is dominated by a lowland topography with a sloping to steep morphological condition. In general, the plains on the island of Bunguran Besar have a plains topography with altitudes ranging from 5- 30 meters above sea level, and the highest altitude is on Mount Ranai, 920 meters above sea level. This condition causes environmental problems, especially on the plains that form basins with geodes that affect the condition of easily polluted groundwater resources influenced by the presence of shallow and close to the surface groundwater (aquifer). The condition of the aquifer, which is shallow and relatively close to the surface, has the potential for groundwater contamination by polluting sources. This study aims to determine the potential spatial groundwater pollution using the SINTACS method hydrogeological approach based on this background. The SINTACS method is a vulnerability approach by assigning a value and weight to each parameter or triggering the vulnerability. The primary data used for the vulnerability assessment were phreatic groundwater depth, soil texture, and slope. Meanwhile, the parameters of the infiltration conditions, the aeration conditions of the rocks, the compiler of lithology, and the hydraulic conductivity (K) or the passing of water in the rock were obtained from the secondary data approach. The scenario of groundwater pollution vulnerability uses the normal scenario impact approach. It is known that the condition of low vulnerability is 28% or an area of 486 km2, medium vulnerability is 20% or an area of 343.8 km2, high vulnerability is 0.04% or an area of 0.7 km2, and very high vulnerability is 52% or an area of 898.7 km2. In general, the condition of vulnerability in Bunguran Besar Island is very high.